Substitution of the Fermented Cocoa Pod Waste in to the Grass Based Diet on Performance of Bligon Goat - Engkus Ainul Yakin; Sri Sukaryani; Catur Suci Purwati (Buletin Peternakan, 2021)
This experiment was aimed to evaluate the effect of fermented cocoa pod as feed for Bligon goats. Sixteen Bligon goat with a body weight of 11-13 kg were put into individual cages which were equipped with feed and drink containers. The study design used a randomized block design, where initial body weight in as peragam with four treatments and four replications. Fermented cocoa pod used Trametes versicolor. The experimental treatments were T1= 30% of fresh king grass + 50% of dried king grass + 20% of concentrate; T2= 30% of fresh king grass + 30% of dried king grass + 40% of concentrate; T3= 30% of fresh king grass + 30% of cocoa pod + 40% of concentrate; and T4= 30% of fresh king grass + 30% of cocoa pod fermented + 40% of concentrate. Observed variables were feed intake, body weight gain and feed conversion. The result showed that fermented cocoa pod at the level of 30% had higher (P<0.05) infeed intake (560.33 g day-1), body weight gain (101.79 g head-1day-1), and feed conversion (5.50) compared to other treatments. The conclusion of this study were the use of 30% cocoa pod fermented in the ration showed the best body weight gain and feed conversion on Bligon goat performance.